DiDang Tang Inhibits Endoplasmic Reticulum Stress-Mediated Apoptosis Induced by Oxygen Glucose Deprivation and Intracerebral Hemorrhage Through Blockade of the GRP78-IRE1/PERK Pathways - Huang, Qingxia; Lan, Tianye; Lu, Jing; Zhang, He; Zhang, Dongmei; Lou, Tingting; Xu, Peng; Ren, Jixiang; Zhao, Daqing; Sun, Liwei; Li, Xiangyan; Wang, Jian (Frontiers in Pharmacology, 2018)
DiDang Tang (DDT), a Chinese traditional medicine formula, contains 4 Chinese traditional medicine substances, has been widely used to treat intracerebral hemorrhage (ICH) patients. However, the molecular mechanisms of DDT for protecting neurons from oxygen and glucose deprivation (OGD)-induced endoplasmic reticulum (ER) stress and apoptosis after ICH still remains elusive. In this study, high-performance liquid chromatography fingerprint analysis was performed to learn the features of the chemical compositions of DDT. OGD-induced ER stress, Ca2+ overload, and mitochondrial apoptosis were investigated in nerve growth factor -induced PC12, primary neuronal cells, and ICH rats to evaluate the protective effect of DDT. We found that DDT treatment protected neurons against OGD-induced damage and apoptosis by increasing cell viability and reducing the release of lactate dehydrogenase. DDT decreased OGD-induced Ca2+ overload and ER stress through the blockade of the glucose-regulated protein 78 (GRP78)- inositol-requiring protein 1α (IRE1)/ protein kinase RNA-like ER kinase (PERK) pathways and also inhibited apoptosis by decreasing mitochondrial damage. Moreover, we observed similar findings when we studied DDT for inhibition of ER stress in a rat model of ICH. In addition, our experiments further confirmed the neuroprotective potential of DDT against tunicamycin (TM)-induced neural damage. Our in vitro and in vivo results indicated that the neuroprotective effect of DDT against ER stress damage and apoptosis occurred mainly by blocking the GPR78-IRE1/PERK pathways. Taken together, it provides reliable experimental evidence and explains the molecular mechanism of DDT for the treatment of patients with ICH.